Essential operations management - Hill, Alex; Hill, Terry (New York, United States : Palgrave Macmillan, 2011)
From two highly respected authors in the field, Essential Operations Management provides a concise, student-friendly overview of operations management, striking a balance between coverage of the service and manufacturing industries that reflects current trends and supported by well-developed international case studies and learning features
Includes bibliographical references and index
Keywords: Industrial management; Production management